If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 + -6x = 10 + 2x Reorder the terms: 5 + 3x + -6x = 10 + 2x Combine like terms: 3x + -6x = -3x 5 + -3x = 10 + 2x Solving 5 + -3x = 10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 5 + -3x + -2x = 10 + 2x + -2x Combine like terms: -3x + -2x = -5x 5 + -5x = 10 + 2x + -2x Combine like terms: 2x + -2x = 0 5 + -5x = 10 + 0 5 + -5x = 10 Add '-5' to each side of the equation. 5 + -5 + -5x = 10 + -5 Combine like terms: 5 + -5 = 0 0 + -5x = 10 + -5 -5x = 10 + -5 Combine like terms: 10 + -5 = 5 -5x = 5 Divide each side by '-5'. x = -1 Simplifying x = -1
| -2(z+3)-z=-z-5(z+2) | | x^6+3x^3-4= | | 17x=8x+8 | | -2*-4=o | | 4x-2+2x-5=77 | | 4(5z-1)-5(2+9)=2(z+1) | | 2*-4=o | | -2*-4=ourfgn | | sin(7x)=cos(7x) | | (2d^2-9d)-(-4d^2+20d+17)= | | 2x+(18-x)=11 | | 6(-2)=r+5r | | P(x)=(60x-0.3x^2)-(5x+13) | | 3x+1/3=3x-1/2 | | ln(16x)= | | 5x+14=2+7x | | -1(-1)=z | | 2cos(3x-1)=0 | | 32=2(x+4.5) | | (c^2-9c-5)-(-c^2-8c-10)= | | (x-4)2=(x-2)2 | | x^2-10*x+13=0 | | x^2-10*x+13= | | 7v-28=9+3v-1 | | (11b^2-7)+(15b^2-b)= | | (6y-8)+(5y-3)+(6y+4)=180 | | 50=.5*20V^2 | | -26.3+0.1p=0.9+5.3 | | 2y-5x=-8 | | x*x+4x+1=32 | | -12.1+0.5p=0.9+5.3 | | ln^5+ln(2x)=5 |